THE INFLUENCE OF THE MORPHOLOGICAL CHARACTERISTICS ON THE PRECISION OF THROWNIG THE BALL INTO THE BASKET AMONG THE PLAYERS AGED BETWEEN TWEELVE AND FOURTEEN - Boris Nikolić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
The paper deals with the influence of the morphological characteristics on the precision of throwing the ball into the basket among the players aged between twelve and fourteen. The research has been carried on the sample of a hundred boys (basketball players). The system of predictable variables consists of thirteen anthropometric measures. The research has one variable that is related to the ability of the boys to handle with a certain situation and to their agility. The influence of the predictable variables on the variable of criterion has been established by the standard analysis of regression. It has been established that the system of anthropometric measures directly affected the ability of the examinees to score a point without moving, and that the same thing happened when the players changed the straight direction without the use of the basketball table. The key words in this paper are: basketball, morphological characteristics, the ability to handle with certain situation, precision, prediction, criterion